Clinical condition and cardiovascular risk factors displaying neoatherosclerosis in stented coronary arteries with developing restenosis - V. P. Mazaev; A. A. Komkov; S. V. Ryazanova (Кардиоваскулярная терапия и профилактика, 2016)
Aim. To study the significance of clinical parameters and cardiovascular risk factors (CVR) for restenosis development at long terms after percutaneous coronary intervention (PCI) as a possible displaying of neoatherosclerosis development (NA).Material and methods. Totally, 155 patients after coronary stents implantation, bare and drug eluting, who then, according to clinical profile, underwent second (follow-up) coronary arteriography (CAG) and/or PCI at the timeline of ~4 years. All patients were selected to groups according to restenosis development and time spent before the second procedure (before and after 9 months): group 1 (n=67) — short term follow-up (<9 months) and absence of restenosis; group 2 (n=26) — short period with restenosis; group 3 (n=43) — long term (>9 months) and absence of restenosis; group 4 (n=19) — long term and restenosis (probable NA).Results. Comparison of clinical data and CVR showed that hypodynamia/ abdominal obesity were more prevalent in the group 1 — 20,90%/11,94%, respectively, and group 3 — 13,95%/11,63%, than in group 4 — 5,26%/5,26% and were completely absent in group 2 (p=0,011). Second PCI at the follow-up was done significantly more commonly in restenosis: gr.1/gr.3 — 68,66%/58,14%, gr.2/gr.4 — 84,62%/89,47% (p=0,028). Diagnosis “acute coronary syndrome” in “follow-up CAG/PCI” was significantly more common in delayed restenosis as a display of possible NA — group 4 — 31,58%, comparing to other groups of patients: group 1 — 14,93%, group 2 — 11,54%, group 3 — 4,65% (p=0,043). Other risk factors: arterial hypertension, hypercholesterolemia, diabetes mellitus, insulin dependency, chronic renal failure, smoking, alcohol abuse, family cardiovascular anamnesis, body mass index, — did not show statistically significant differences between the groups.Conclusion. Neoatherosclerosis as the possible element of restenosis at long terms of coronary stenting, in difference from earlier restenosis, presented with more frequent acute clinical conditions. There were no significant difference by CVR factors.